Hydrothermal synthesis and structural characterization of ammonium ion-templated lanthanide(III) carboxylate-phosphonates - Ayi, Ayi A.; Kinnibrugh, Tiffany L.; Clearfield, Abraham (Frontiers in Chemistry, 2014)
Using N (phosphonomethyl)iminodiacetic acid (H4PMIDA), as a complexing agent, two new complexes, (NH4)La(PMIDA)(H2O)•H2O, 1 and (NH4)Yb(PMIDA), 2 have been synthesized hydrothermally. In both compounds, the metal ions are trapped in a three five-membered chelate rings by the chelating PMIDA anions giving a bi-capped trigonal prism LaO8N and capped trigonal prism YbO6N geometries for 1 and 2, respectively. The structure of 1 consists of La(PMIDA)(H2O) chelating units, linked together by the phosphonate oxygen atoms O1 and O3 to form a double chain along the c-axis. The double chains are then connected together by the bridging phosphonate oxygen O2 to form a 2D layered structure with alternating 4- and 8-membered apertures.The structure of 2 consists Yb(PMIDA) chelating units, which are connected by alternating bridging carboxylate and phosphonate groups along the [010] direction forming chains with a corrugated pattern. The third phosphonate oxygen bridges the chains together along the [001] direction to build the two-dimensional layer with 4 and 6 membered apertures in the bc plane. Under excitation of 330nm, compound 2 shows a broad emission band at λmax = 460nm, This emission is essentially in the blue luminescent region, which corresponds to ligand centered fluorescence.